Resilience for all/resiliencia para todos: achieving justice for Latinx communities following the 2013 Colorado floods - Truslove, Micaela, author; Malin, Stephanie A., advisor; Luna, Jessie K., committee member; Browne, Katherine E., committee member (Colorado State University. Libraries, 2022)
Environmental justice arose out of people's and communities' needs to address concrete problems of inequitable environmental exposures and contamination. However, resilience scholarship has largely failed to engage with the environmental justice (EJ) literature, and resilience remains a highly contested term that fails to adequately address issues of vulnerability and power. A holistic view of EJ—community-based and focused on distributive, procedural, and recognition elements of outcomes and practices—helps assess justice aspects of resilience-building, especially when used in conjunction with a community capabilities focus. I build on these points by arguing that an EJ framework provides an ideal lens through which to explore social justice in community engagement around resilience-building to climate-related events. This study uses data from a critical discourse analysis, semi-structured interviews, and a multi-dimensional environmental justice (EJ) framework coupled with Matin et al.'s (2018) concept of "equitable resilience" to explore how Latinx cultural brokers and resilience practitioners in Boulder County, Colorado are making disaster preparedness and community resilience-building efforts more just and equitable following a devastating flood event. Most importantly, I find that cultural brokers' participatory and inclusive form of community-building work—and the community that emerges from such work—is resilience. I also find that, although Boulder County resilience-building efforts are moving toward more just and equitable practices, cultural brokers and resilience practitioners face systemic and institutionalized barriers to fully realizing distributive, procedural, and recognition justice and increasing community capabilities. Lastly, I show that cultural brokers use small but powerful acts of counterstorytelling, or testimonios, in predominantly white spaces to expose and unsettle entrenched power structures. An EJ framework used in conjunction with the concept of equitable resilience can help resilience and disaster practitioners assess and improve their resilience and disaster preparedness programming and efforts. This study also contributes to the disaster and community resilience scholarship by providing a new way to evaluate community resilience-building efforts using a critical EJ-capabilities lens. This approach addresses issues of distributive, recognition, and procedural (in)justice as well as attending to underlying power imbalances and inequality that can limit community capabilities.
Keywords: cultural brokers; discourse; qualitative methods; disasters; community resilience; environmental justice